Cytochrome c‐based domain modularity governs genus‐level diversification of electron transfer to dissimilatory nitrite reduction. (11th December 2014) - Aas, Finn Erik; Li, Xi; Edwards, James; Hongrø Solbakken, Monica; Deeudom, Manu; Vik, Åshild; Moir, James; Koomey, Michael; Aspholm, Marina
Summary The genus Neisseria contains two pathogenic species (N. meningitidis and N. gonorrhoeae) in addition to a number of commensal species that primarily colonize mucosal surfaces in man. Within the genus, there is considerable diversity and apparent redundancy in the components involved in respiration. Here, we identify a unique c‐type cytochrome (cN) that is broadly distributed among commensal Neisseria, but absent in the pathogenic species. Specifically, cN supports nitrite reduction in N. gonorrhoeae strains lacking the cytochromes c5 and CcoP established to be critical to NirK nitrite reductase activity. The c‐type cytochrome domain of cN shares high sequence identity with those localized c‐terminally in c5 and CcoP and all three domains were shown to donate electrons directly to NirK. Thus, we identify three distinct but paralogous proteins that donate electrons to NirK. We also demonstrate functionality for a N. weaverii NirK variant with a C‐terminal c‐type heme extension. Taken together, modular domain distribution and gene rearrangement events related to these respiratory electron carriers within Neisseria are concordant with major transitions in the macroevolutionary history of the genus. This work emphasizes the importance of denitrification as a selectable trait that may influence speciation and adaptive diversification within this largely host‐restricted bacterial genus.